ANALYSIS OF HIGH SCHOOL STUDENT'S KNOWLEDGE OF RECOGNIZING EUCLIDEAN ELEMENTS - Harisman, Yulyanti; Putri, Sri Adinda (KALAMATIKA Jurnal Pendidikan Matematika, 2024)
Euclid's Elements is a work written by an ancient Greek mathematician named Euclid in the 3rd century BC. It is one of history's most famous and influential mathematical works, serving as a significant basis for studying geometry and number theory for centuries. This research aims to describe Euclid's Elements and determine the extent of high school students' knowledge about Euclid and his work and their level of understanding in solving mathematical problems. This qualitative research utilizes case study methods and literature reviews. Data were collected through problem-solving exercises and interviews. Thematic data analysis was conducted to elucidate Euclid's Elements and students' level of knowledge. The case study involved presenting mathematics problems and interviewing five high school students, using assessment instruments incorporating problem-solving and open interviews. The findings reveal that many students lack familiarity with the elements of Euclid's Elements but demonstrate proficiency in solving mathematical problems related to it.